Correlation of maternal and early neonatal outcome with strength of lower segment caesarean section scar on abdominal ultrasonography - Bhakti Kalyankar; Vijay Kalyankar; Shrinivas Gadappa; Kokila Ashok Gaikwad (Barpeta Obstetrics and Gynaecological Society, 2021)
Objectives: To assess the strength of lower uterine segment caesarean section scar after 36 completed weeks up to 40 weeks with the help of transabdominal ultrasonography (USG) and correlating with maternal and early neonatal outcome in patients with previous one LSCS. Methods: This prospective study was carried out in the Department of OBGY, GMCH, Aurangabad from 1st October 2017 to 1st October 2019. All these cases underwent transabdominal USG between 36 completed weeks to 40 weeks and scar finding noted. Based on scar thickness, cases were assigned into two groups of ≤ 3 mm and > 3 mm. TOLAC (Trial of labor after caesarean) was given to cases having scar thickness > 3 mm and elective LSCS was done in scar thickness ≤ 3 mm. Correlation of maternal and fetal outcome with caesarean section scar strength parameters were done. Results: Total 211 cases were included in present study. 83 cases had scar thickness ≤ 3mm (39.3%) and 128 cases had scar thickness >3mm (63.6%). Strong association was seen between scar thickness and scar shape, border, continuity and echogenicity.105(49.76%) cases were given TOLAC with successful VBAC (Vaginal birth after caesarean), in 83(39.33%) cases had repeat elective LSCS, and 23(10.90%) cases had failed TOLAC with repeat emergency LSCS. 20 neonates needed NICU (Neonatal intensive care unit) care but causes of it were not related to scar complications. No case of obstetric hysterectomy, maternal mortality or still birth in our study. Conclusion: Successful VBAC may be advocated considering clinical factors, counseling and vigilant intrapartum management along with scar thickness of > 3mm, in tertiary care centres.